I'dâd al-Mawâd al-Ta'lîmiyyah li Mahârati al-Kalâm Fî Dhoui al-Madkhal al-Wadzhîfî Fî Maskan al-Khairiyyah Sukorejo Situbondo - Shofwatul Fu’adah (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2021)
Learning materials are very important in learning Arabic. But in reality, there are many learning processes that do not use even do not have the right textbooks or teaching materials, like the researcher found in Al-Khoiriyah Ma’hadul Qur’an dormitory Sukorejo Situbondo. This was impacting on their lack of speaking skills, while they have to communicate in Arabic and English everyday as bilingual dormitory. Therefore, they need specific learning textbooks so that teaching and learning activities can be directed correctly, especially the textbooks that can support learning maharah kalam, so they can improve their speaking skills. This study aims to preparation textbooks of maharah kalam using functional approach because students need materials that related with their daily activities and functional verbal expressions. The method of this research was research and development (R&D)"which was proposed by Borg and Gall. The design of the product trial went through the expert validation, content and instructional design expert. The results of this textbook trial showed that this textbook was effective to meet the students need to increase speaking skills which using pre-test and post-test exercise, with pre-test result from 58,6 then increase in post test to be 85 and also the result of the teachers and students questionnaire is very good and effective to use after using this product. Therefore the teaching materials useful for their Arabic daily communication